1998
DOI: 10.1029/97gl03765
|View full text |Cite
|
Sign up to set email alerts
|

Initial results from WING, the continuous GPS network in the western Pacific area

Abstract: Abstract.To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 16 publications
4
37
0
Order By: Relevance
“…Current rates along the fault are in the order of or lower than the 5 mm/yr proposed by Allen et al (1994) and Wang et al (1998) using geological data. This corroborates differential motions from GPS measurements in eastern Tibet (King et al, 1997;Wang et al, 1998) but contradicts assumptions by others (Zhao, 1995;Peltzer and Saucier, 1996). Results from recent measurements in a local GPS network along the southern part of the Red River Fault suggest similar, low motion (if any) along this part of the fault .…”
Section: 2supporting
confidence: 76%
See 1 more Smart Citation
“…Current rates along the fault are in the order of or lower than the 5 mm/yr proposed by Allen et al (1994) and Wang et al (1998) using geological data. This corroborates differential motions from GPS measurements in eastern Tibet (King et al, 1997;Wang et al, 1998) but contradicts assumptions by others (Zhao, 1995;Peltzer and Saucier, 1996). Results from recent measurements in a local GPS network along the southern part of the Red River Fault suggest similar, low motion (if any) along this part of the fault .…”
Section: 2supporting
confidence: 76%
“…This suggests that the area west of the Xiaojiang Fault and Kunming and east of the eastern syntaxis of India moves southward with a rate of approximately 15 mm/yr with respect to SSC (see King et al, 1997, for comparison). This confirms that a major part of the differential motion between Lhasa and Kunming is accommodated by rotation about the eastern syntaxis of India (King et al, 1997;Ratschbacher et al, 1996).…”
Section: The Red River Fault Differential Motion Between the Stationssupporting
confidence: 68%
“…Recent GPS measurements revealed that both the Philippine Sea plate and the Mariana Ridge are moving westward relative to the Eurasia [Kato et al, 1998;Sella et al, 2002], and the opening of the Mariana Trough occurs because the movement of the former is faster than the latter. This observation is not consistent with the opening model assuming a trench rollback [Martinez and Fryer, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…[11] The data were analyzed as daily global solutions using the GAMIT/GLOBK software [King and Bock, 1999;Herring, 1999] to combine regional data with data from up to 80 IGS stations. We solved for a free network global polyhedron which we then aligned with the ITRF97 [Boucher et al, 1999] by computing Helmert transformations on the coordinates and velocities of the 47 class A and B core IGS sites [Altamimi, 1998].…”
Section: Geodetic Datamentioning
confidence: 99%